Sexual abuse - Johnson, Jerry L. (Allyn & Bacon casebook series, 2007)
A multi-systemic approach to practice / Jerry L. Johnson & George Grant, Jr. -- Kate / Jan Wrenn -- Austin / Cathy Simmons -- Dani / Leslie Menhart -- Mary / Cathy Simmons